Towards Putting a Price on the Risk of Bank Failure - Daniel Snethlage (New Zealand Government, The Treasury, 2015)
This paper develops a new approach for conceptualizing and measuring the risk associated with bank failure. The price of this risk in risk-adjusted present-value terms is estimated at 170-340 million per annum (0.07-0.15% of GDP), representing the price of the financial risk that exists ex-ante (ie, before a bank fails). This can be interpreted as the cost that is either passed onto the banks via higher funding costs, or borne as an implicit risk on the government's balance sheet. Alternatively, one could think of this as a one-off cost, in the event that all major banks failed in a single crisis. If that were to happen, and if net losses were to be 5-10 per cent of bank liabilities the total cost could be 16-31 billion (7-13% of GDP). This can be interpreted as either the net cost of a government bail-out, or the total value of haircuts on wholesale and retail creditors that would be applied under an Open Bank Resolution (OBR) or a liquidation. Bank bail-outs are not necessarily required or recommended in New Zealand given the existence of OBR. However, the major banks currently receive a one-notch uplift in their credit ratings specifically because of the expectation of government support. These ratings' uplifts are used to estimate the market-implied likelihood that the banks would be bailed out in the event of their failure, and therefore the size of the implicit guarantee banks that are seen to receive. This perceived implicit guarantee is estimated to be worth around 80-230million per annum (0.04%-0.11% of GDP), equivalent to a 3-8 basis points subsidy on banks' total borrowing costs. This estimate is low by international standards, consistent with the current soundness of the major domestic banks and the relatively low perceived likelihood of government support.
Keywords: G21; G38; H89; 330; Bank failure; contingent liabilities; implicit guarantee; financial crises; bail-out; bail-in; bank resolution; Bankenkrise; Haftung; Kreditrisiko; Schuldenübernahme; Finanzkrise; Bankenregulierung; Neuseeland